Характерные числа в моделях описания производственных систем - Пигнастый, Олег Михайлович (Національний аерокосмічний університет ім. М. Є. Жуковського "Харківський авіаційний інститут", 2006)
Производственная система предприятия представлена как система с большим количеством элементов, которые являются объектами труда. Отличительные числа производственной системы вводятся с помощью статистической механики. Такой подход дает возможность качественной оценки функционирования производственных процессов, обоснованного выбора соответствующих уравнений набора макроскопических параметров весов для описания реального производственного объекта. Оценка выбора модели должна интерпретироваться как качественная. Подход имеет преимущество в простом сравнении результатов, соответствующих различным микроскопическим моделям.

The production system of an enterprise is represented as the system with a large number of elements, which are the objects of one's labour. The distinctive numbers of the production system are introduced by means of statistical mechanics. This approach gives the possibility of qualitative estimation of production processes functioning, sound selection of the corresponding equations set of macroscopic parameters balances for a description of real production object. The estimation of the model selection should be interpreted as the qualitative one. The approach has the advantage of an easy comparison of the results, corresponding to different microscopic models.
Characteristic numbers in production system description models
Keywords: производственная линия; тип производства; PDE-модель производства; PDE-модели поточных линий; незавершенное производство; массовое производство; балансовые уравнения; квазистатический процесс; технологический процесс; subject of labour; work in progress; stochastic process; kinetic equation; conveyor; production system; mass production; management system; balance equations of the production line; equation of state; discrete-event model; model fluid; clearing-function; quasi-static process; transient process; production line; PDE-model of production; balance equations; production management system